Measuring the Macroeconomic Performance of Public Finance Management - Pulay, Gyula; Simon, József (Public Finance Quarterly, 2020)
In international practice, the performance of public finance management is usually assessed on the basis of quality indicators of the subsystems of the public finance system. The experts of the State Audit Office of Hungary have developed an evaluation system capable of measuring the performance of public finance management on the basis of quantitative indicators and quantifying the contribution of the factors that determine performance most. This article describes this system. It also shows how the assessment system was used to analyse the risks to the ongoing reduction of Hungarian public debt.